A general approach for population games with application to vaccination - Reluga, Timothy C. (2011)
Reconciling the interests of individuals with the interests of communities is a major challenges in designing and implementing health policies. In this paper, we present a technique based on a combination of mechanistic population-scale models from Markov decision process theory and game theory that facilitates the evaluation of game theoretic decisions at both individual and community scales. We demonstrate how nonlinear population models can be combined with game theory to inform the management of infectious diseases. To illustrate our technique, we provide solutions to several variants of the simple vaccination game including imperfect vaccine efficacy and differential waning of natural and vaccine immunity. In addition, we show how path-integral approaches can be applied to the study of models in which strategies are fixed waiting times rather than exponential random variables. These methods can be applied to a wide variety of decision problems with population-dynamic feedbacks.